Quality of life of children with idiopathic nephrotic syndrome according to clinical types - Sang Ngoc Nguyen; Viet Quoc Tran; Quang Van Vu (Vietnam Journal of Science, Technology and Engineering, 2018)
Idiopathic nephrotic syndrome (INS) is a major manifestation of chronic idiopathic glomerulonephritis and a common disease in children. The cause and pathogenesis of the disease have not been clarified so far. The treatment is usually a longterm process, from a few months to several years, even decades, including the period of hospitalisation, outpatient treatment period and follow-up period after treatment. The INS patients are negatively affected by the disease and its treatment process. The aim of this study is to assess the health-related quality of life (QOL) of children with INS according to clinical types in Haiphong Children’s Hospital. Object: Describe some factors related to the QOL of children with INS. Subjects: 71 patients diagnosed with INS, who are being monitored and treated at Haiphong Children’s Hospital from 10/2015 to 05/2016. Methods: Prospective studies, descriptive cross-sectional. QOL of the patients is assessed by the PedsQL 4.0 scale; the higher score shows that the lower QOL. Results: The general QOL score of children with INS (21.24±13.91) was higher than normal children (16.98±10.20). Children with steroid-resistant INS have a higher score (31.62±14.32) than children with steroid-dependent (20.57±9.08) and responsive INS (14.58±6.83). The QOL score of children with one of the symptoms Cushing’s face, hirsutism or acne are significantly higher than children without the corresponding symptoms. Children who finished their treatment had a lower score (15.47±7.42) than children being treated (21.33±10.23). The average QOL score has a linear correlation with the duration of INS. Conclusion: The general QOL of children with INS substantially declined compared with that of healthy children. The QOL of children with steroid-dependent and resistant INS is lower than that of the children with steroid-responsive type. The QOL of children with one of the symptoms Cushing’s face, hirsutism or acne is significantly lower than that of children without the corresponding symptoms. The QOL of children who completed treatment is higher than the group being treated. The longer the duration of treatment, the more the children’s QOL declined.